Digital Passages: Migrant Youth 2.0. Diaspora, Gender and Youth Cultural Intersections - Leurs, Koen (MediaMatters, 2015)
Increasingly, young people live online, with the vast majority of their social and cultural interactions conducted through means other than face-to-face conversation. How does this transition impact the ways in which young migrants understand, negotiate, and perform identity? That's the question taken up by Digital Passages: Migrant Youth 2.0, a ground-breaking analysis of the ways that youth culture online interacts with issues of diaspora, gender, and belonging. Drawing on surveys, in-depth interviews, and ethnography, Koen Leurs builds an interdisciplinary portrait of online youth culture and the spaces it opens up for migrant youth to negotiate power relations and to promote intercultural understanding.